Complete genome sequence of an avian metapneumovirus subtype A strain isolated from chicken (Gallus gallus) in Brazil - Rizotto, Laís S.; Scagion, Guilherme P.; Cardoso, Tereza C. [UNESP]; Simão, Raphael M.; Caserta, Leonardo C.; Benassi, Julia C.; Keid, Lara B.; Oliveira, Trícia M.F. de S.; Soares, Rodrigo M.; Arns, Clarice W.; Borm, Steven Van; Ferreira, Helena L. (American Society for Microbiology, 2017)
We report here the complete genome sequence of an avian metapneumovirus (aMPV) isolated from a tracheal tissue sample of a commercial layer flock. The complete genome sequence of aMPV-A/chicken/Brazil-SP/669/2003 was obtained using MiSeq (Illumina, Inc.) sequencing. Phylogenetic analysis of the complete genome classified the isolate as avian metapneumovirus subtype A.